Effects of single and combined immunotherapy approach targeting amyloid β protein and α‐synuclein in a dementia with Lewy bodies–like model. Issue 9 (1st August 2019) - Mandler, Markus; Rockenstein, Edward; Overk, Cassia; Mante, Michael; Florio, Jazmin; Adame, Anthony; Kim, Changyoun; Santic, Radmila; Schneeberger, Achim; Mattner, Frank; Schmidhuber, Sabine; Galabova, Gergana; et al.
Abstract: Introduction: Immunotherapeutic approaches targeting amyloid β (Aβ) protein and tau in Alzheimer's disease and α‐synuclein (α‐syn) in Parkinson's disease are being developed for treating dementia with Lewy bodies. However, it is unknown if single or combined immunotherapies targeting Aβ and/or α‐syn may be effective. Methods: Amyloid precursor protein/α‐syn tg mice were immunized with AFFITOPEs® (AFF) peptides specific to Aβ (AD02) or α‐syn (PD‐AFF1) and the combination. Results: AD02 more effectively reduced Aβ and pTau burden; however, the combination exhibited some additive effects. Both AD02 and PD‐AFF1 effectively reduced α‐syn, ameliorated degeneration of pyramidal neurons, and reduced neuroinflammation. PD‐AFF1 more effectively ameliorated cholinergic and dopaminergic fiber loss; the combined immunization displayed additive effects. AD02 more effectively improved buried pellet test behavior, whereas PD‐AFF1 more effectively improved horizontal beam test; the combined immunization displayed additive effects. Discussion: Specific active immunotherapy targeting Aβ and/or α‐syn may be of potential interest for the treatment of dementia with Lewy bodies.